Estudio de prefactibilidad para la instalación de una planta procesadora de colchones para cama de espuma visco elástica - Strobbe Barbat, Caterina Milena (2018)
In Peru, the mattress market has kept a steady 10% annual growth, representing a higher rate than current population growth. Innovation and new materials technology go hand by hand with economic growth in Peru, where socioeconomic segment C has strengthened and gained aspirations for quality life improvement and the economic resources to do it. On the market side, the consumer is generally familiar with innerspring mattresses, but there is a tendency towards looking for wellbeing improvement in A, B and C socioeconomic segments, being our target market. The brand name is a decisive factor in the buying decision, as an indicator of the product´s quality and durability. Sale price for a twin-size mattress (size that represents 30% of market sales) was estimated at PEN 1 200, in order to position the brand together with premium brands such as Komfort and Rosen. First year´s demand is estimated at 6 926 units, with a steady annual growth of 5%, to achieve sales of 10 885 units by year 10. The factory will be located at Chilca, a developing industrial area with an investment of USD 150 per square meter, which is considerably lower compared to other industrial zones. The unemployment rate in this area is 40%, providing the factory with a sufficient supply of labor willing to work in that zone. On the supply side, 99% of sales are produced locally, Productos Paraíso del Peru is the market leader with 55% of participation with its two main brands: Paraíso and Zebra. Raw material and supplies will be obtained from local market to have a fast response to a sudden shift in demand. The company´s value added is to offer 100% memory foam mattresses, avoiding the use of springs in to diminish rebound and vibrations. The factory´s installed capacity is 21 530 mattresses per year, thus year 1 would occupy 21% of total capacity and would raise to 44% by year 10, with the possibility of further growth. The total investment for the project is PEN1,9 million, which is obtained 40% by stockholders (with an opportunity cost of 25%) and 60% by debt (with a 20% interest rate). The project is economically and financially feasible and attractive, with a positive NPV and with an economic IRR of 57% and a financial IRR of 98%, both higher than the opportunity cost. The analysis is projected to 10 years in order to achieve brand maturity and investment return time is favorable, being less than three years. The project´s most sensitive variable is the demand. The projected market share is 1,5%. If market share falls to 1,1%, probability of NPV being positive is 80%. The project has also a positive social value, as for every PEN of investment, there is a return of PEN 12 of social added value. In conclusion, the project is feasible, as there is a relevant market, with acquisitive power, willing to buy the product. Factory investment is also economically and financially feasible, as the sale price for the product will be high, thus leaving high margins. The required technology in order to manufacture the product in an efficient way that reduces fixed and variable costs is existent.